PICKY EATING BEHAVIOR ON THE INCIDENT OF STUNTING IN CHILDREN TODDLERS IN TIRTOMOYO, WONOGIRI - Sutanto, Alfiani Vivi; Nurhidayah, Lia Ratih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: The process of development and growth during toddlerhood is determined by the food consumed every day. Giving the body the appropriate nutrition it needs will produce good development. However, various obstacles often occur, such as eating disorders in children. One of the eating disorders in children is the habit of refusing food and being picky about food, often called picky eating, which will have an impact on their nutritional status. Thin or poor nutritional status in children under five can put them at risk of stunting. Stunting is a physical growth disorder characterized by a decrease in growth rate and the impact of a nutritional imbalance.Methods: This research is quantitative, with a type of observational analytical research. This research was conducted from January to October 2023 in Tirtomoyo, Wonogiri, with a population of 55 children and a sample of 50 children. A questionnaire was developed by researchers based on the Picky Eating Behavior Rating Scale and Transcultural Nursing Theory. Whereas the connection between variables is analyzed using the analysis of simple linear regression through ANOVA and power tables, the influence between variables is observed through the model summary table on value correlation (R). The license number of research is 071/277.Result: There is an influence of the behavior of picky eaters against the incidence of stunting among toddlers in the Tirtomoyo, Wonogiri, with a level of significance (Sig.) of 0.004 and a value coefficient determination (R square) of 0.164.Conclusion: The behavior of picky eaters can influence the incidence of stunting in children. Keywords: Behavior picky food (Picky Eating), Stunting, Toddlers